The Development of Binocular Suppression in Infants - Yang, Jiale; Kanazawa, So; Yamaguchi, Masami K. (Frontiers in Psychology, 2020)
Little is known about the time of development of the binocular suppression. In the present study, we evaluated the emergence of binocular suppression in infants by using continuous flash suppression (CFS, Tsuchiya & Koch, 2006). In our experiment, one eye of infants presented with a static face image at one side of the screen, while another eye is presented with dynamic Mondrian patterns in full screen. Adult observers confirmed that the static face image was consciously repressed by the changing Mondrian patterns. If binocular suppression were functional, the infant would not perceive the face as did the adults, and thus would not show any preference in the experiment. However, if binocular suppression in the infants were not yet acquired, they would perceive the face and the Mondrian patterns at the same time, and would thus show preference for the side where the face was presented. The results showed that infants aged 2–3 months, but not those aged 4–5 months, detected the position of the face. Furthermore, this detection was not due to weak contrast sensitivity to the dynamic Mondrian mask. These results indicated that the immature binocular visual system may perceive different images from different eyes simultaneously, and that infants may lose this ability after establishing binocular suppression at 4–5 months of age.